Peningkatan Pemahaman Mahasiswa melalui Belajar Aktif (Active Learning) dengan Pengembangan Algoritma dan Membahasakan Ide-Ide dari Konsep-Konsep dan Prinsip-Prinsip pada Mata Kuliah Kalkulus 1 - Kharis, Muhammad (Kreano, Jurnal Matematika Kreatif-Inovatif, 2011)
Mathematical concepts are hierarchically structured, which means that in studying mathematics, the prerequisites concepts must be completely understood in order to understand the further concepts. This research is a classroom action research by applying active learning methods to express the ideas of the concepts and principles in calculus. This research aims to find a learning form that can give student a chance to express the ideas of the concepts and principles in calculus. This research also aims to know the learning outcomes from applying this methods. The research was conducted in three cycles. Each cycle consists of planning, execution, observation, and reflection. Each cycle begins with the pre test and ends with a post test. Pre tests are used to determine the preparation of students in the lecture, while the post test to determine student learning outcomes. Keywords: penelitian tindakanÃ‚Â  kelas, siklus, pre tes, pos tes, belajar aktif.